Chemoenzymatic Approaches to the Synthesis of the Calcimimetic Agent Cinacalcet Employing Transaminases and Ketoreductases. Issue 11 (28th February 2018) - Marx, Lisa; Ríos‐Lombardía, Nicolás; Farnberger, Judith F.; Kroutil, Wolfgang; Benítez‐Mateos, Ana I.; López‐Gallego, Fernando; Morís, Francisco; González‐Sabín, Javier; Berglund, Per
Abstract: Several chemoenzymatic routes have been explored for the preparation of cinacalcet, a calcimimetic agent. Transaminases (TAs) and ketoreductases (KREDs) turned out to be useful biocatalysts for the preparation of key optically active precursors. Thus, the asymmetric amination of 1‐acetonaphthone yielded an enantiopure ( R )‐amine, which can be alkylated in one step to yield cinacalcet. Alternatively, the bioreduction of the same ketone resulted in an enantiopure ( S )‐alcohol, which was easily converted into the previous ( R )‐amine. In addition, the reduction was efficiently performed with the KRED and its cofactor co‐immobilized on the same porous surface. This self‐sufficient heterogeneous biocatalyst presented an accumulated total turnover number (TTN) for the cofactor of 675 after 5 consecutive operational cycles. Finally, in a preparative scale synthesis the TA‐based approach was performed in aqueous medium and led to enantiopure cinacalcet in two steps and 50% overall yield. Abstract :